The news and structural style in the poem of Ibn Zurayq Al-Baghdadi (La Taathleh) - Eddin Wahid Elhouary, Salah; Hussein Abbood Al-Hilali, Safaa (Edelweiss Applied Science and Technology, 2024)
This research deals with the two styles of news and composition in Ibn Zuraiq Al-Baghdadi’s poem (Do not torture him); These two styles are the pillars of Arabic speech and the basis of its discourse, and each of them has linguistic, grammatical, stylistic, and rhetorical characteristics that distinguish it from the other. In this research, we will discuss the definition of the two styles in language and terminology, and provide a brief overview of the poet mentioned in our research. Then we will move on to mention the declarative places, as well as the constructional ones, and how Ibn Zuraiq al-Baghdadi used them in each place, and the reasons for his use of each style. And exploring the aesthetics of all of the above to conclude a set of results in which we mention the aesthetics of each style in poetic discourse, and the extent of this poet’s ability to employ methods to attract the recipient’s attention towards what he presented. The aim of the study is to highlight the stylistic and rhetorical features of the two styles as well, and to work on analyzing the aforementioned verses, including predicates or constructions. It should be noted that there are verses that contain both styles, so we will analyze the style in which we see the appropriate or strongest significance, even though we have analyzed the two styles in a way that we hope to It will be enough. After that comes the list of sources and references that we have adopted in this research. They are diverse sources and references, including traditional, rhetorical, grammatical, and contextual sources, as well as the books of hadith scholars due to their importance in rhetorical and contextual studies.